Circular Economy as a Model of Achieving Sustainable Development - Roleders, Viktoriia; Oriekhova, Tetyana; Zaharieva, Galina (Problemy Ekorozwoju, 2022)
In this paper the essence of the concept of circular economy was determined. The processes of transition to a circular economy are analyzed, as a result of which three levels are distinguished: efficient use of materials; product life extention; smart production and use of products. The connection between the circular economy and sustainable development was implemented. The main business models of the circular economy are considered: Resources recovery, Sharing platforms, Product life extension, Product as a service, Circular suppliers. Strategies and tools of circular economy are developed. The world experience of waste utilization is considered.